Bride Trafficking from Vietnam to China: The Critique of Socialist Feminism - Jessenia Destarini Asmoro (Global South Review, 2023)
Bride trafficking is a phenomenon where women are sold for forced marriage. This phenomenon occurs in many Vietnamese women brought to China without their consent to marry. It has been claimed that there are 'supply and demand factors in encouraging the development of bride trafficking from Vietnam to China, such as an imbalanced sex ratio in China and a lack of education. This research analyses the occurrence of bride trafficking from Vietnam to China through the lens of gender and politics. Using the narrative analysis method and literature study through the perspective of socialist feminism, this research found that bride trafficking from Vietnam to China embodies double oppression towards Vietnamese women. It results from the intersection between two oppressive structures: patriarchy and capitalism.Consequently, a practice of sexual economy is developed in the form of bride trafficking. This research also found that globalization significantly affects bride trafficking from Vietnam to China. Globalization paves the way for this phenomenon to happen. Thus, this article offers a perspective favouring women in analyzing transnational phenomena in international relations.Keywords: bride trafficking; globalization; patriarchy; capitalism; sexual objectification